Upregulated TRAIL and Reduced DcR2 Mediate Apoptosis of Decidual PMN-MDSC in Unexplained Recurrent Pregnancy Loss - Li, Congcong; Zhang, Xiaoxin; Kang, Xiaomin; Chen, Chao; Guo, Feng; Wang, Qiaohong; Zhao, Aimin (Frontiers in Immunology, 2020)
Myeloid-derived suppressor cells (MDSC), especially polymorphonuclear MDSC (PMN-MDSC), accumulate in maternal-fetal interface during pregnancy and are involved in the maintenance of immune tolerance. Decreased PMN-MDSC is associated with pregnancy complications such as unexplained recurrent pregnancy loss (URPL). In the present study we showed decreased PMN-MDSC in the URPL group compared with the normal pregnancy (NP) group, and PMN-MDSC was the major subset of MDSC in human decidua with potent immune suppression activity. We then performed gene expression profile and found that human decidual PMN-MDSC in the NP and URPL groups showed different gene and pathway signature, including apoptosis. Apoptosis of decidual PMN-MDSC was mediated by TNF-related apoptosis–induced ligand (TRAIL) in a Caspase 3 dependent manner. TRAIL expression was detectable in decidua and upregulated in decidua of the URPL group. Notably, of all the membrane TRAIL receptors, only DcR2 was downregulated in PMN-MDSC in the URPL group. In vitro experiment demonstrated that DcR2 blockade sensitized PMN-MDSC to TRAIL-mediated apoptosis. Together, these data indicate that increased TRAIL and reduced DcR2 on PMN-MDSC sensitize PMN-MDSC response to TRAIL-induced apoptosis in the URPL group, which is responsible for decreased accumulation of PMN-MDSC in URPL.